ANALISIS PERAN STAKEHOLDERS DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA JATIREJO, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Fahad Mursyid Jannata; Aufarul Marom; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Developmnent is not only in the infrastructure sector, but also in various fields including tourism. One of the tourism destinations in Semarang City is the Jatirejo Tourism Village. In the beginning, the management of this tourist village was quite good, but as the years goes by, ii is safe to say that the management weren't as optimal as it should be. This is caused by weak coordination between tourism stakeholders for synchronization and harmonization. This research aims to identify stakeholders in policy implementation, identify stakeholders in tourism deelopment, analyze the role af stakeholders, and analyze supporting and inhibiting factors in tourism development in Jatirejo Tourism Village. This research conducted by qualitative descriptive method by collecting data through observation, interviews and documentation. The result of the research shows that the stakeholders in implementing the Pentahelix-shaped policy consist of academics, by Kedaireka Team; from the private sector, represented by BNI: from the community, involving Pokdarwis Jatirejo, Karang Taruna Jatirejo, PKK Jatirejo, KTT